PELAKSANAAN FUNGSI PEMANTAUAN DAN EVALUASI DPD RI TERHADAPRAPERDA DAN PERDA DALAM RANGKA HARMONISASI LEGISLASI NASIONAL DAN DAERAH - Wiyono, Bambang; Darusman, Yoyon Mulyana; Susanto, Susanto (NATIONAL JOURNAL of LAW, 2022)
The existence of laws and regulations at the regional level is essentially a resultof the implementation of the principle of decentralization in the administration of local government. According to Article 1 point 8 of Law Number 23 of 2014 concerning Regional Government (Law Number 23 of 2014), decentralization is the handover of Government Affairs by the Central Government to autonomous regions based on the principle of autonomy. At the same time, in an effort to strengthen the principle of decentralization, the Regional Representative Council (DPD) of the Republic of Indonesia was born. The idea of forming the DPD is the desire for reform due to the social, economic and political crisis that has occurred since 1997 which led to demands for amendments to the 1945 Constitution. laws and principles of the rule of law. In this research, specialists who are taken and used are descriptive analysis, it is said to be descriptive because this research is described in detail and detail, factual and dynamicabout the research studied in this study. This research will explore how the function of monitoring and evaluating Raperda and Perda owned by DPD RI. As stated in Article 249 paragraph (1) letter j, namely: monitoring and evaluating draft regional regulations and regional regulations. The addition of this authority may be an implication of the Constitutional Court (MK) Decision Number 137/PUU- XIII/2015  and Number 56/PUU-XIV-2016 which states that the rules are unconstitutional in Law No. cancellation of legislation. After the Constitutional Court's decision, the Central Government (Minister of Home Affairs or the Governor) has no authority to cancel regional regulations. The regulation and practice of supervision of regional regulations and regional regulations is carried out through preventive supervision and repressivesupervision. Preventive supervision is carried out by the Central Government through the following instruments: consultation or facilitation or evaluation of the draft regional regulation before it is approved by the regional head (executive preview) Keywords: DPD RI, MD3 Law, Raperda, Perda, Monitoring, Evaluation